2008
DOI: 10.1111/j.1464-410x.2008.07515.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of erectile function after nerve‐sparing radical prostatectomy: improvement with nightly low‐dose sildenafil

Abstract: OBJECTIVE To evaluate the effect of low‐dose sildenafil for rehabilitating erectile function after nerve‐sparing radical prostatectomy (NSRP), as the delay to recovery of erectile function after NSRP remains under debate. PATIENTS AND METHODS Forty‐three sexually active patients had a NSRP; at 7–14 days after surgery they had a Rigiscan® (Dacomed Corporation, Minneapolis, MN, USA) measurement of nocturnal penile tumescence and rigidity (NPTR). To support the recovery of spontaneous erectile function, 23 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 24 publications
1
111
0
12
Order By: Relevance
“…43 Penile rehabilitation after nerve-sparing radical prostatectomy: Clinical evidence Despite all the evidence in favor of chronic treatment with PDE5-I, only a few trials have assessed the role of penile rehabilitation in men who underwent RP. [46][47][48][49][50][51][52] Montorsi et al 46 demonstrated that, by using intracorporeal injections of alprostadil early after bilateral NSRP (BNSRP), the rate of recovery of spontaneous erections was significantly higher than the rate with observation alone. Those data also recently were confirmed by Mulhall et al,47 who demonstrated that the prophylactic use of intracorporeal injections of alprostadil in patients who did not respond to oral sildenafil resulted in higher rates of spontaneous functional erections and erectogenic drug response 18 months after NSRP.…”
Section: Pharmacologic Prophylaxis Of Postoperative Erectile Dysfunctmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Penile rehabilitation after nerve-sparing radical prostatectomy: Clinical evidence Despite all the evidence in favor of chronic treatment with PDE5-I, only a few trials have assessed the role of penile rehabilitation in men who underwent RP. [46][47][48][49][50][51][52] Montorsi et al 46 demonstrated that, by using intracorporeal injections of alprostadil early after bilateral NSRP (BNSRP), the rate of recovery of spontaneous erections was significantly higher than the rate with observation alone. Those data also recently were confirmed by Mulhall et al,47 who demonstrated that the prophylactic use of intracorporeal injections of alprostadil in patients who did not respond to oral sildenafil resulted in higher rates of spontaneous functional erections and erectogenic drug response 18 months after NSRP.…”
Section: Pharmacologic Prophylaxis Of Postoperative Erectile Dysfunctmentioning
confidence: 99%
“…50 Recently, Bannowsky et al evaluated the effect of daily sildenafil 25 mg in a small cohort of patients who underwent NSRP and who maintained nocturnal erections early after surgery. 51 Patients assigned nonrandomly to receive either daily sildenafil 25 mg or no treatment after surgery. In that study, the patients who received nightly sildenafil had higher mean IIEF-5 scores and a shorter time to recovery of erectile function (P < .001) compared with the patients who remained untreated after surgery (potency rate, 86% vs 66%, respectively).…”
Section: Pharmacologic Prophylaxis Of Postoperative Erectile Dysfunctmentioning
confidence: 99%
“…69 It has been shown that nightly sildenafil significantly improves nocturnal erections after nerve-sparing prostatectomy, which is theorized to be critical in the penile rehabilitative process by preventing penile hypoxia and resulting fibrosis and veno-occlusive dysfunction. 70,71 This was demonstrated by Montorsi and colleagues, 70 who showed that in more than 70% of patients, the administration of sildenafil produced nocturnal erections that were significantly stronger than those after administration of a placebo. However, it should be emphasized that in this study a number of inclusion and exclusion criteria were followed, producing a selected study population and limiting its findings to a more general patient base.…”
Section: Phosphodiesterase Type 5 Inhibitorsmentioning
confidence: 79%
“…Among elderly patients, the development of hypoxia-induced tissue damage and fibrosis of the corpora cavernosa are the major cause of ED after RP. 23 Reviews of the literatures have shown that age, obesity and urinary tract symptoms are the mostimportant factors attributed to the occurrence of ED. 1,5,[8][9][10]12,23 The appropriate dose of PGE1 used for ED treatment depends on the etiology.…”
Section: Discussionmentioning
confidence: 99%